Use of Fresh Osteochondral Allografts in the Patellofemoral Joint - Lattermann, Christian; Kremser, Victor; Altintas, Burak (The Journal of Knee Surgery, 2018)
Fresh osteochondral allograft (OCA) transplantation has become a mainstay for the treatment of osteochondral defects in the tibiofemoral joint. With excellent outcomes and high survival times, this technology has recently become more interesting for use in the patellofemoral (PF) joint. This review article will point out the historical difficulties that the use of fresh OCA poses. With newer surgical approaches and a better understanding of the mechanical requirements of the PF joint, the use of OCA transplantation has shown increasingly better results. Illustrating the technique for the preparation and implantation of single plug allografts and bulk allografts to the trochlea and patella as well as the analysis of the available literature, we point out the current state of the art as well as potentially achievable long-term results. Finally, we will point out emerging technology seeking to further develop the use of allograft technology in patellofemoral chondral defects.
Keywords: patellofemoral surgery; cartilage; allograft